Emergent Trust and Work Life Relationships: How to Approach the Relational Moment of Trust - Eikeland, Tone Bergljot (Nordic Journal of Working Life Studies, 2015)
How do we trust? What does the basic mechanism of trust look like? These questions define the starting point for a comparison of the classic ideas of how trust works by Mayer et al. (1995), Möllering’s (2006) re-adaption of Giddens’, Simmel’s, and James’ classic ideas of trust, and a phenomenological approach focusing on “emergent trust.” Introducing the concept of emergent trust, the idea is to suggest a phenomenological approach to studies of trust in work-life relationships in professional organizations, as an alternative to trust as a cognitive attitude, where trust becomes a stable, individual possession. The term “emergent” demonstrates a trust that emerges in meetings between persons, it has an immediate, unconditional quality, and shows itself in situations of life where there is a potential for trust to appear. Trust’s basic relationality makes the person morally responsible for the other. Trust appears between persons, as an event, constituting risk and uncertainty as a natural and positive part of our lives. Still, in larger social settings, the responsibility of trust also disperses on to the work itself, and our wider social networks.